2023
DOI: 10.1002/eqe.3941
|View full text |Cite
|
Sign up to set email alerts
|

Harmonizing Seismic Performance via Risk Targeted Spectra: State of the art, dependencies, and implementation proposals

Abstract: Design spectra are commonly defined for a constant value of hazard associated to an “ultimate” limit state (LS) of reference, typically 10% in 50 years. Given a specific structure, this approach results in different limit‐state exceedance risk levels even for sites characterized by the same design peak ground acceleration (PGA), mainly because of differences in hazard curve shape/slope. Instead, Risk Targeted design maps (first applied in ASCE7‐10) suggest the application of suitable spectra adjustment factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It is worth pointing out that, for this comparison, both the risk‐targeted and uniform hazard spectra have shapes directly derived from the calculations, courtesy of the ground motion model(s) therein, without any smoothing adjustments for cosmetic or practical purposes. This was a conscious choice, since other works have shown that the way such spectral shape modifications are implemented has far from negligible effects 13 which are not examined here. For all three sites, the assumptions made about the target reliability against failure, have produced higher risk‐targeted spectral ordinates than the corresponding 475 years return period uniform hazard spectra, across all vibration periods ( T ).…”
Section: Risk‐targeted Vs Uniform‐hazard Designmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth pointing out that, for this comparison, both the risk‐targeted and uniform hazard spectra have shapes directly derived from the calculations, courtesy of the ground motion model(s) therein, without any smoothing adjustments for cosmetic or practical purposes. This was a conscious choice, since other works have shown that the way such spectral shape modifications are implemented has far from negligible effects 13 which are not examined here. For all three sites, the assumptions made about the target reliability against failure, have produced higher risk‐targeted spectral ordinates than the corresponding 475 years return period uniform hazard spectra, across all vibration periods ( T ).…”
Section: Risk‐targeted Vs Uniform‐hazard Designmentioning
confidence: 99%
“…10 This entails choosing an appropriate target rate of failure (often taken as interchangeable with the annual failure probability) to meet said objective, 𝜆 * 𝑓 , and making some a-priori assumptions about the corresponding structural fragility, that is, the conditional probability of failure, given the level of shaking intensity. 11,12 Despite the apparent simplicity of linking the seismic design actions to a risk objective, in practice this approach of deriving, so-called, risk-targeted ground motion (RTGM), presents some issues 13 that this study explores by implementing the original proposal for their derivation by Luco and co-authors, 14 for seven Italian sites. Risk-targeted and uniformhazard elastic design spectra are calculated for these sites and the available results of a recent research project are used to simulate the design of low-and mid-rise reinforced concrete (RC) moment-resisting frames at each site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The paper by Suzuki et al, 21 provides opinions on the forces opposing seismic design paradigm shifts in Japan, which is certainly interesting beyond Asia, and is likely applicable to all countries of advanced technical culture. Finally, the work of Spillatura et al 22 provides a comprehensive overview of risk-targeted ground motion (RTGM). RTGM was the subject of several submissions, showing that this is one of the prominent approaches towards implementing risk-targeted design since the seminal work of Luco et al 23 (Nevertheless, some limitations, which seem not to completely solve the issues with the current approach to seismic design, and some assumptions-mainly on the fragility of the designed structure-may still require developments.…”
mentioning
confidence: 99%